Overcrowded 14,14′‐Bidibenzo[a,j]anthracenes: Challenges in Syntheses and Atypical Property of Lacking Symmetry‐Breaking Charge Transfer (SBCT) - Pan, Ming‐Lun; Hsu, Chao‐Hsien; Lin, Yan‐Ding; Chen, Bo‐Han; Lu, Chih‐Hsuan; Yang, Shang‐Da; Chou, Pi‐Tai; Wu, Yao‐Ting (Chemistry : a European journal, 2024)
14,14′‐Bidibenzo[a,j]anthracenes (BDBAs) were prepared by iridium‐catalyzed annulation of 5,5′‐biterphenylene with alkynes. The molecular geometries of overcrowded BDBAs were verified by X‐ray crystallography. The two dibenzo[a,j]anthryl moieties are connected through the sterically hindered 14 positions, resulting in highly distorted molecular halves. The conformation with a small twist angle between two molecular halves can minimize steric conflicts between the substituents at 1 and 13 positions and the carbon atoms of the central axis, as well as steric clashes between those substituents. One such example is octafluoro‐substituted BDBA, where the interplanar angle between two anthryl moieties is approximately 31° (currently the lowest reported value, cf. 81° in 9,9′‐bianthracene). The intramolecular interactions and electronic couplings between two molecular halves resulted in upfield 1H NMR signals, redshifted absorption and emission bands, and a reduced HOMO–LUMO gap. Photodynamic investigations on BDBAs indicated that the formation of the conventional symmetry‐breaking charge transfer (SBCT) state was suspended by restricted rocking around the central C−C bond. Such a mechanism associated with this highly constrained conformation was examined for the first time. The overcrowded biaryl bears two highly distorted molecular halves and a small interplanar angle between two anthryl moieties (31°, currently the lowest reported value). The close contact between the two aryl fragments endows them with intramolecular interactions. Whereas the restricted rocking around the central C−C bond suspends the formation of the symmetry‐breaking charge transfer (SBCT) state.